2014
DOI: 10.1161/strokeaha.114.005713
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Cluster Randomized Trial in Stroke Secondary Prevention Using Electronic Health Records

Abstract: Stroke represents a long-term condition that requires ongoing preventive medical care to reduce the risk of recurrence of stroke. During the first 10 years after stroke, there is nearly 40% cumulative risk of recurrence.1 Secondary prevention after stroke should include interventions to manage and monitor vascular risk factors including blood pressure (BP), lipid-lowering drugs, and antithrombotic treatment where appropriate, as well as efforts to control overweight, increase exercise, and reduce alcohol and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 24 publications
(22 reference statements)
0
37
0
Order By: Relevance
“…These cluster trials were in implementation research focusing on primary care management and appropriate prescribing for respiratory infections 82 and stroke secondary prevention. 83 Van Staa et al 84 reported on two pilot clinical trials to evaluate statin prescribing for CVD prevention and antibiotic prescribing for chronic obstructive pulmonary disease. Such trials are sometimes referred to as 'point-ofcare' trials because recruitment, randomisation and outcome evaluation are all conducted in the context of routine service delivery settings.…”
Section: Rapid Trials Using Electronic Health Recordsmentioning
confidence: 99%
“…These cluster trials were in implementation research focusing on primary care management and appropriate prescribing for respiratory infections 82 and stroke secondary prevention. 83 Van Staa et al 84 reported on two pilot clinical trials to evaluate statin prescribing for CVD prevention and antibiotic prescribing for chronic obstructive pulmonary disease. Such trials are sometimes referred to as 'point-ofcare' trials because recruitment, randomisation and outcome evaluation are all conducted in the context of routine service delivery settings.…”
Section: Rapid Trials Using Electronic Health Recordsmentioning
confidence: 99%
“…49 Recently, the CPRD has begun to be used as a resource for interventional research. 16,[50][51][52]…”
Section: Cluster Randomised Trialmentioning
confidence: 99%
“…It is very widely used internationally for epidemiological research [21], and even for clinical trials. This includes the recruitment of patients through their electronic health records (EHRs) for a pharmacogenetic study of statin-induced myopathy [22], the conduct of cluster randomised trials [23], and pragmatic pointof-care trials randomising patients between different standard treatments [24].…”
Section: The United Kingdommentioning
confidence: 99%